Anatomical modifications in the cell wall of guava as influenced by calcium - Natale, William (2005)
The objective of this work was to evaluate modifications in cell walls of guava fruits produced either under liming or not. The study made use of fruits of the Paluma cultivar harvested from nonlimed and limed areas. Fruits harvested from the calcium treated plants had cell walls and the middle lamella well defined and soundly structured. Fruits from the nontreated plants showed poorly structured cell walls and middle lamella. The application of calcium has an important effect on the subcellular structural organization of guava fruit and on the increase of fruits shelf life.